Pulmonary cancer and hypertrophic osteoarthropathy brief recurrence of the osteoarticular symptoms after surgical ressection - Pereira, José Rodrigues; Aguiar Neto , José Ribeiro; lkari, Flora Kazumi; Nikaedo, Suely Mayumi (São Paulo Medical Journal, 1995)
A case of adenocarcinoma of the lung in a 57 years old patient associated with hypertrophic ostearthropathy is reported by the authors. The paraneoplastic manifestation occurred after the pulmonary symptoms and receded spontaneously after a right inferior lobectomy was performed. Osteoarticular symptoms returned near after a tumoral recurrence. Articular pains disappeared 48 hours after the tumoral recurrence ressection of the chest wall and clubbing disappeared completely after the 3rd. week.